2011
DOI: 10.1007/s12043-011-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electrical and optical studies on spray-deposited aluminium-doped ZnO thin films

Abstract: Thin films of zinc oxide (ZnO) were deposited on cleaned glass substrates by chemical spray pyrolysis technique using Zn(CH3COO)2 as precursor solution. Also, aluminium-doped thin films of ZnO were prepared by using AlCl3 as doping solution for aluminium. The dopant concentration [Al/Zn atomic percentage (at%)] was varied from 0 to 1.5 at% in thin films of ZnO prepared in different depositions. Structural characterization of the deposited films was performed with X-ray diffraction (XRD) studies. It confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…This must be due to the oxygen deficiency of the material [25]. When we plot a graph between log( ) and 10 3 /1000/T(K −1 ), we obtain the activation energy from the slope of the graph and it comes out to be 0.27 eV which is also in good agreement with the result reported earlier [26].…”
Section: (Ii) Sem Resultssupporting
confidence: 88%
“…This must be due to the oxygen deficiency of the material [25]. When we plot a graph between log( ) and 10 3 /1000/T(K −1 ), we obtain the activation energy from the slope of the graph and it comes out to be 0.27 eV which is also in good agreement with the result reported earlier [26].…”
Section: (Ii) Sem Resultssupporting
confidence: 88%
“…Thus, it can be concluded that the lattice disorder that happens at higher Zn concentration than 6% may be due to the ionic radius difference between Zn 2+ and Zr 4+ ions. Tewari et al reached a similar conclusion for Aldoped ZnO [55].…”
Section: Fig 2 Xrd Of 6%zn/sz Calcined At (A) 500 °C (B) 600 °C Amentioning
confidence: 57%
“…In general, the oxygen moieties are adsorbed on the ZnO thin film surface, in turn changes the resistance of the thin film. reaction with the target gas and give away an electron to the ZnO surface giving rise to change in resistance [15,16]. The ratio of the resistance measured in vacuum to the resistance measured in testing gas atmosphere is called as sensitivity.…”
Section: Resultsmentioning
confidence: 99%